2012
DOI: 10.1051/0004-6361/201219147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas toward G18.8+1.8

Abstract: Aims. This work aims at investigating the characteristics of the molecular gas associated with the nebula G18.8+1.8, which is linked to the Wolf-Rayet star HD 168206 (WR 113), and its relation to other components of its local interstellar medium. Methods. We carried out molecular observations of the 12 CO(J = 1−0) and (J = 2−1) lines with an angular resolution of 44 and 22 using the SEST telescope. Complementary NANTEN data of the 12 CO(1−0) line were also used. The dust emission was analyzed using Spitzer-IRA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2014
2014
2015
2015

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Dense molecular condensations (or clumps) lying at the border of Galactic Hii regions are therefore among the most likely sites for stellar births, and hence, where to look for early stages of star formation (e.g. Cappa et al 2009;Vasquez et al 2012;Deharveng et al 2012;Duronea et al 2014). In recent years, the triggered star formation process, especially the C&C mechanism, has been studied extensively at the edges of many bubble-shaped Hii regions such as RCW 79,RCW 120, The LABOCA map (data corresponding to Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dense molecular condensations (or clumps) lying at the border of Galactic Hii regions are therefore among the most likely sites for stellar births, and hence, where to look for early stages of star formation (e.g. Cappa et al 2009;Vasquez et al 2012;Deharveng et al 2012;Duronea et al 2014). In recent years, the triggered star formation process, especially the C&C mechanism, has been studied extensively at the edges of many bubble-shaped Hii regions such as RCW 79,RCW 120, The LABOCA map (data corresponding to Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Dense molecular condensations (or clumps) lying at the border of Galactic Hii regions are then among the most likely sites for stellar births, and hence, to look for early stages of star formation (e.g. Cappa et al 2009;Vasquez et al 2012;Deharveng et al 2012;Duronea et al 2014). In recent years, the triggered star formation process, especially the C&C mechanism, has been studied extensively on the edges of many bubble-shaped Hii regions such as Sh2-104, RCW 79, Sh2-212, RCW 120, Sh2-217, Sh2-90 (Deharveng et al 2003, 2008Zavagno et al 2006Zavagno et al , 2010Brand et al 2011;Samal et al 2014), as well as in several surveys (e.g Thompson et al 2012;Simpson et al 2012) Gum 31 is one of the many southern Galactic Hii regions that appear as a ring at infrared (IR) wavelengths (see the upper panel of Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when massive stars form inside a molecular cloud it is expected that they dominate the state of the parental cloud and consequently the stellar formation process within. It has been shown that a large fraction of stars originate at the peripheries of Hii regions (Pomarès et al 2009;Cappa et al 2009;Deharveng et al 2010Deharveng et al , 2012Vasquez et al 2012). Tables 5 and 6 are available in electronic form at http://www.aanda.org…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when massive stars form inside a molecular cloud it is expected that they dominate the state of the parental cloud and consequently the further stellar formation process within. Indeed, it has been shown that a large fraction of stars originates at the peripheries of Hii regions (Pomarès et al 2009;Romero & Cappa 2009;Cappa et al 2009;Deharveng et al 2010;Vasquez et al 2012;Deharveng et al 2012). Having this in mind, it is instructive to study the molecular gas adjacent to Hii regions since it can provide important information on the interaction between massive stars and their natal environments.…”
Section: Introductionmentioning
confidence: 99%
“…Concluyeron que la nebulosa está en una etapa intermedia entre las fases de conservación de la energía y de conservación de momento. Los resultados fueron reunidos en el trabajo Vasquez et al (2008).…”
Section: Antecedentesunclassified